Sirtuin1, Inducible Nitric Oxide Synthase in Newly Diagnosed Iraqi Diabetic Patients - Hazim, Mahmood Abdulhameed; Saifullah, Perry H; Abd, Beydaa Ahmed (Al-Nahrain Journal of Science, 2018)
In Mammals Sirtuins (SIRTs) are members of the silent information regulator two family Sirtuin1 regulate a variety of cellular functions. It shows anti-oxidative, anti-inflammatory, and anti-apoptotic effects against cellular damage.SIRT1 conserves the cells by the mitochondrial biogenesis organizing, cellular energy and oxido reduction state. Vascular tissues are protected by SIRT1 too. In diabetic patients mutation in exon1 of SIRT1 (L107P) in insulin-generating cells conducted in over production of nitric oxide synthase (iNOS), TNF-α.Assessment of SIRT1 protein levels in newly diagnosed Iraqi diabetic in regards to family history Age, gender, and duration of disease, and its correlation with biochemical parameter in the same group. Measurement of iNOS, TNF-α.This study involved totally 40 volunteers. This group were subdivided (20) volunteers as newly diagnosis (DMT1) duration disease ˂1 year, group1 was subdivided to 10 male and 10 female: (10 with family history and 10 without family history) and group two healthy volunteers. Group1 All DMT1 were under insulin treatment. Healthy Volunteers (20) included in this study as control groups. None Healthy Volunteers were alcoholic, smoke, or having a history of (CVD) cardiovascular disease, thyroid disease, and hormonal abnormalities problems were exempted from this study.In the present study SIRT1, TNF-alpha, iNOS were measured by enzyme linked immune absorbent assay (ELISA). Biochemical parameters fasting glucose, body mass index (BMI), urea, creatinine and lipid profile that were measured by spectrophotometer technique in patients and healthy volunteers groups.The Statistical Analysis System- SAS (2012) program was used to effect of difference factors in study parameters. Least significant difference –LSD test (ANOVA) was used to significant compare between means. Estimate of correlation coefficient between difference parameters in this study.The results showed that a highly significant increase in levels of FBG, Urea, creatinine and lipid profile except HDL was decrease levels, BMI was decrease in newly diagnosis DMT1 with healthy volunteers groups. A significant decrease in SIRT1 protein, and a highly significant increase in TNF-alpha and iNOS in newly diagnosis DMT1 with healthy volunteers groups. A highly negative significantly correlation coefficient between SIRT1 and F.G., TG., VLDL,TG/HDL, A.I. and negative significantly correlation duration, urea, creatinine,T.CH., LDL. And non-significant correlation with age, BMI, HDL, CH/HDL and LDL/HDL.. Effect of gender were insignificant of SIRT1. Effect of family history in patients. SIRT1 were all insignificant in patients with family history as with non-family history group. SIRT1 could decreases in the sera of DMT1 patients with family history, the decreased SIRT1 level reflect a mutation in SIRT1 gene, the decreases in SIRT1 on increases the incident of DMT1 complication.